A Note on Measurement of Skewness - Fogler, H. Russell; Radcliffe, Robert C. (Journal of Financial and Quantitative Analysis, 1974)
Certainly, the concept of skewness of returns and its role in the context of portfolio analysis has gained increasing attention in recent literature. Witness the studies by Alderfer and Bierman [1], Arditti [2, 3], Jean [4], and Simonson [5]. Each of these studies has treated skewness as the third moment of a series expansion—accordingly, skewness has been measured and interpreted as a logical extension of the traditional two-dimensional return-versus-standard deviation analysis of security evaluation.